Screening young athletes - can we ignore that a negative standalone history & physical examination could skip high risk cardiac conditions ? - Stoian, I. M.; Ionescu, A.; Stoian, I.; Georgescu, M. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Pre-Participation (PPE) cardiovascular (CV) screening in young athletes is the cornerstone of any evaluation for detecting high-risk CV (hrCV) conditions responsible for sudden cardiac death (SCD) linked with exercise.(2,5) Sometimes, the PPE-CV protocols rely on the standalone History&Physical (H&P),such as the 14-Element AHA Recommendation.(4) Less apparent hrCV conditions may not be readily evident by standalone H&P (1); the association with resting electrocardiography (ECG) and echocardiography (ECHO) is mandatory for the correct diagnosis. Retrospective study of PPE-CV athletes:To compare the standalone H&P (14-Element) with ECG and ECHO results, recorded for each athlete, according to the protocol. To evaluate the incidence of false positive (positive: >/equal 1 of the 14-Elements) (4) and false negative H&P vs ECG/ECHO data. METHODS: Retrospective 6-year (2016-2021) study of 385 highly trained athletes (ath)-football . Study Group:211 ath (100% males;17-37 yo); 178 (84.4%) caucasians, 33 (15.6%) afroamericans. All underwent PPE before competitions. Standard PPE included H&P, ECG (3) and ECHO (5). RESULTS: Height 174+/-2 cm; Weight 78+/-1 kg; BSA 1.94 m2;BP 125+/-5 mmHg. 211 ath: 191 (90.52%),normal H&P and ECG; 4(1.89%) positive H&P; 16(7.6%) normal H&P and borderline ECG (in time,1 Brugada type I, 3 WPW). ECHO:200(94.7%) normal with normal H&P and 11 (5.3%) abnormal with 4 positive H&P: 2 hypertrophic cardiomyopathy, 2 right ventricular dilation, 1 abnormal origin of coronary artery, 1 dilated cardiomyopathy, 3 stenotic bicuspid aortic valve, 2 mitral prolapse. Coronarography, cardiac MRI indicated accordingly. CONCLUSION: In most cases, standalone H&P correlated with ECG and ECHO , but failed to identify hrCV entities responsable for SCD in 11(5.31%; 1 Brugada, 3 WPW, 7 abnormal ECHO). No false positive H&P. Asymptomatic rare cardiac conditions are sometimes overlooked by standalone H&P. Conclusions. PPE-CV screening for identifying hrCV conditions shall include ECG/ECHO.